FORMATION OF CALCULATING SKILLS OF PRIMARY SCHOOL PUPILS BY MEANS OF MULTIMEDIA - Borisenko, М.Ю. (Journal of Information Technologies in Education (ITE), 2015)
The features of the effective implementation of multimedia in the teaching of arithmetic for primary school pupils are shown in the paper. The types of calculating methods are defined. The theoretical framework of these methods consists of: specific content of arithmetic operations,properties of arithmetic operations, connections between components and the results of arithmetic operations, change of a result of arithmetic operations depending on change in one component, the numeration of numbers, number rules, etc. The possibility of forming of these calculating methods for primary school pupils by means multimedia technologies is demonstrated. Some requirements that should be considered during the designing of dynamic models and simulators are given. These dynamic models and simulators are implemented for enhancing of various processes of thinking and perception for primary school pupils. Some samples of organization of the pupils’ cognitive activity with applying of simulators, dynamic models and presentations are shown. The necessity of implementing of multimedia for developing of pupils’ cognitive activity during learning arithmetic in primary school is underlined. Methodological recommendations for multimedia applying during explaining arithmetic operations to primary school pupils (1-4-th grades) are presented. The effectiveness of the applying of multimedia technology in the learning process at primary school is confimed by results of forming stage of the pedagogical experiment